Negotiating multiple perspectives: a discussion of instructors' practice within an English-language service course. Issue 3 (4th May 2017) - Watson, Danielle
Abstract: At the University of the West Indies, large courses often require the involvement of multiple persons in their delivery. Within the English Language Foundation Unit, several of the courses offered cater to over 500 students in any given semester. The large number of students necessitates multiple practitioners providing instructions as part of the same course offering. While stylistics may vary, there is the need for course instruction and content to depict uniformity. Practitioners' conceptualization of a specific topic will inform the instruction received by students. In instances where practitioners do not conceptualize content in a like manner, students within the same course may receive varied instruction, thus affecting student output and overall evaluation. The paper looks specifically at a service course offered at the University of the West Indies and the practices of the multiple persons involved in the teaching of the course. It provides an overview of practitioners' discussion of their conceptualization of content areas within the courses and assesses the extent to which there are variations and/or similarities. It also discusses how these impact teaching and learning. The research seeks to derive an actionable direction for collaboration and further discussions within large service courses with the aim of improving teaching and learning.